Analysis of the implementation of business ethics and strategic management in companies in Indonesia - Fransisca, Vika; Kholipah, Siti Ainul (Asian Journal of Social and Humanities, 2024)
The purpose of this study is to analyze the implementation of business ethics and strategic management in companies in Indonesia. The method used in this study is a descriptive method with a qualitative approach. Data collection techniques use documentation techniques. Data analysis is inductive / qualitative and the results of qualitative research emphasize meaning rather than generalization, namely triangulation (combined) techniques. The results of the study found that the analysis of the implementation of business ethics and strategic management in companies in Indonesia confirms that business ethics is a very important aspect for the survival of the company. Companies that apply business ethics well can build trust from colleagues, the community, and customers, which is an important capital to maintain business continuity. Therefore, companies have a responsibility to maintain and improve standards of business ethics to achieve sustainable growth. On the strategic management side, its role is also very important in achieving the company's long-term goals, adapting to changes in the business environment, and directing human resources. By implementing good business ethics and effective strategic management, companies in Indonesia can better face business challenges and contribute to sustainable economic growth.